On the Ground: 40B Developments Before and After. - DeGenova, Alexandra.; Goodwin, Brendan; Moriarty, Shannon.; Robitaille, Jeremy. (Tufts University. Tisch Library., 2018)
2009 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Citizens' Housing and Planning Association.